Comorbid Normal Pressure Hydrocephalus with Parkinsonism: A Clinical Challenge and Call for Awareness - A. Cucca; M. C. Biagioni; K. Sharma; J. Golomb; R. M. Gilbert; A. Di Rocco; J. E. Fleisher (Case Reports in Neurological Medicine)
Idiopathic normal pressure hydrocephalus (iNPH) is the most common cause of hydrocephalus in adults. The diagnosis may be challenging, requiring collaborative efforts between different specialists. According to the International Society for Hydrocephalus and Cerebrospinal Fluid Disorders, iNPH should be considered in the differential of any unexplained gait failure with insidious onset. Recognizing iNPH can be even more difficult in the presence of comorbid neurologic disorders. Among these, idiopathic Parkinson’s disease (PD) is one of the major neurologic causes of gait dysfunction in the elderly. Both conditions have their peak prevalence between the 6th and the 7th decade. Importantly, postural instability and gait dysfunction are core clinical features in both iNPH and PD. Therefore, diagnosing iNPH where diagnostic criteria of PD have been met represents an additional clinical challenge. Here, we report a patient with parkinsonism initially consistent with PD who subsequently displayed rapidly progressive postural instability and gait dysfunction leading to the diagnosis of concomitant iNPH. In the following sections, we will review the clinical features of iNPH, as well as the overlapping and discriminating features when degenerative parkinsonism is in the differential diagnosis. Understanding and recognizing the potential for concomitant disease are critical when treating both conditions.